THE PENTAHELIX MODEL IN ACCELERATING STUNTING REDUCTION IN EAST LOMBOK DISTRICT - Muhammad Irham Hadi; Utang Suwaryo; Muradi Muradi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
This study aims to analyze the Pentahelix Model in Accelerating Stunting Reduction in East Lombok Regency. This research uses a case study qualitative research approach. Researchers obtained data through observation, interviews, documentation of the subjects and objects of this study. The results of this study are that the problem of stunting in East Lombok Regency has decreased, this is because it is inseparable from the collaboration between various elements such as government, academics, communities, entrepreneurs, and others in order to accelerate the reduction of stunting in East Lombok Regency. In fact, the success of East Lombok Regency in reducing stunting rates won 1st place in the performance evaluation assessment of the implementation of 8 convergence actions in accelerating stunting reduction at the district / city level throughout NTB in 2024.